Analisis Pengaruh Kepemilikan Asing, Ukuran Perusahaan, Komite Audit, Dewan Komisaris Terhadap Sustainability Report - Retnoningsih, Sri; Fikri, Rizal Khurriyatul; Khoiriyah, Khoiriyah; Khoirotunnisa, Khoirotunnisa (Unversitas Islam Madura, 2024)
The topic of this research is disclosure of sustainability reports. This research aims to examine the influence of foreign ownership, company size, audit committee and board of commissioners on the disclosure of sustainability reports on the 2022 Asean Corporate Governance Scorecard. Sustainability reports in this research are measured using the Global Reporting Initiative (GRI) Index. Sample selection used a purposive sampling method with a total sample of 31 companies. The data used in this research is secondary data. The data analysis technique uses multiple linear regression. The research results show that foreign ownership and the board of commissioners have no influence on sustainability report disclosure, on the contrary, company size and audit committee influence sustainability report disclosure.